Design and performance evaluation of a double stator single rotor radial flux pm generator / Annas Alamshah - Annas, Alamshah (2018)
Different Types of generator for wind power usage have become research for many people and researchers. This various generator has been researched for the application of radial flux wind turbines small scale. A double stator single generator has been proposed as an alternative solution in relation to the cost and performance of such systems. However, the greatest emphasis in the report have is the design and performance evaluation of a double stator single rotor radial flux PM generator. The parameter that include in doing the comparisons is frequency, speed ,torque ,current ,voltage and type of motor . Chapter 2 will go through literature a review on past research on this topic. Principles of structure of generator that is axial , radial flux and also with focus on how the generator works by research on the characteristics of the generator with an emphasis on challenges between double stator generator. Different factor of electrical machine that being see is a focus on double stator single rotor configurations, in winding are showed. In Chapter 3, a thoroughly review of the methodology and method which include the method on how to convert or the process of making the motor from single stator to double stator and also testing that need to be test . Next, in chapters 4, an analytical and comparison being done through several test and comparison of the characteristics of the motor between the two type of motor. Studies are validated by comparing the measured value between two type of motor that is single stator and double stator with output power, frequency, voltage and current of the motor being accounted . Based on the results obtained, the speed and voltage that a stator can achieve for a double stator generator will be transform into graph and make a comparison. Lastly in Chapter 5 a conclusion of research that being done will be made based on result in chapter 4 that have been obtained also recommendation than can be improved in future research